Enlisting the Truth of Damnation: the Rhetoric of Wulfstan’s Lifelong Engagement with Eschatology - Federica Di Giuseppe (Filologia Germanica, 2024)
Around the year 1000, England is in a state of crisis and demoralisation which most likely fosters apocalyptic anxieties. The preoccupation becomes prominent in the writings of contemporary vernacular homilists, and plays a key role in Archbishop Wulfstan’s eschatological preaching. By focusing on his use of the list of sinners, this paper illustrates the evolution of Wulfstan’s apocalypticism throughout his career, from ideological conviction to rhetorical tool. In particular, I intend to focus on how the alliterating catalogue, which first appears in De Fide Catholica (Bethurum sermon no. 7, p. 163 and ll. 128-134), is then reworked not only in the longest version of the Sermo Lupi ad Anglos (Bethurum sermon no. 20, p. 273 and ll. 161-166) but also in Wulfstan’s legal writings and political tracts (in which case the list comes to describe earthly sinners, namely criminals proper). The way the catalogue is rephrased signals a change in Wulfstan’s eschatological tone, which is ever-present but still loses its immediacy as the years, his career and the Viking invasions wear on.